Brand Experience and Brand Loyalty: The Mediating Role of Brand Love and Susceptibility to Normative Influence - Akbar Prakosa, Muhammad Rizki; Kuswati, Rini (Yayasan Pendidikan Bukhari Dwi Muslim, 2025)
Purpose: This research analyzes the effects of brand experience on brand loyalty for Le Minerale products, considering the mediating roles of brand love and susceptibility to normative influence. Six hypotheses are formulated to explore direct and indirect relationships among the variables. Research Method: A quantitative approach is employed, utilizing an online survey. The sample consists of 173 university students in Indonesia who have consumed Le Minerale. Purposive sampling is used. Data analysis is conducted with Partial Least Squares Structural Equation Modeling (PLS-SEM) using SmartPLS 3.0. Seventeen indicators are used to measure Brand Experience, Brand Love, Brand Loyalty, and Susceptibility to Normative Influence. Results and Discussion: Brand Experience positively influences Brand Love, which affects both Brand Loyalty and Susceptibility to Normative Influence. Susceptibility to Normative Influence also directly impacts Brand Loyalty. Mediation analysis reveals that Brand Love mediates the effect of Brand Experience on Brand Loyalty, while Susceptibility to Normative Influence mediates the relationship between Brand Love and Brand Loyalty. Implications: The study highlights the significant role of emotional and social influences in Le Minerale’s marketing. Future research should consider broader populations and additional variables, such as brand trust and social media engagement, to gain a more comprehensive understanding of the topic.